AN ANALYSIS OF RELATIVE CLAUSES MADE BY THE EIGHT GRADE STUDENTS OF SMP NEGERI 3 SELAT IN ACADEMIC YEAR 2017/2018 - Martarini, Ni Made Lisma (Yavana Bhasha : Journal of English Language Education, 2019)
The present study is dealt with An Analysis of Relative Clauses Made by the Eight Grade Students of SMP Negeri 3 Selat in Academic Year 2017/2018. The researcher was interested in making an analysis of Relative clauses made by the students under study. The present study is intended to assess the acquisition of relative clauses made by the eighth-grade students of SMP N 3 Selat Karangasem in academic year 2017/2018. In other words, this study is to figure out the ability of the subject under study in understanding relative clauses. The present’s study which use ex-post facto research design with descriptive analysis was intended to answer the following research question: to what extent is the acquisition of relative clauses made by the eighth-grade students of SMP N 3 Selat Karangasem in academic year 2017/2019? In order to answer the research question before, the data were required for the present study which in the form of raw score is showing the ability of the students in mastering relative clauses, were collected by administering the valid and reliable research instrument in form of multiple-choice test items. Then the data is analyzed by using Norm-Reference measure with five standard values. The populations of the present study are the eighth-grade students of SMP Negeri 3 Selat which consist of 206 students. They are considered to have heterogeneous characteristics. In this study 30 students are considered as a sample of the study by using random sampling technique. The data of the study is clearly showed that: (1) there are 4 students or (13.33%) out of 30 students under study who showed excellent ability of relative clauses. (2) There are 4 students or (13.33%) out of 30 students under study who showed good ability of relative clauses (3) there are 10 students or (33.33%) out of 30 students under study who showed sufficient ability of relative clauses. (4) There are 12 students or (40%) under 30 students under study who showed insufficient ability of relative clause. (5) No one students or (0%) out of 30 students who showed poor ability of relative clauses. In the result of the study were used as the basses to assign level/grade to the subject under study, there are 12 students or 40% out of 30 students under investigation who fail in learning and acquiring relative clauses. It means that 40% of them still have low ability. The finding of the present study can be used as the basses in planning much better language teaching especially in mastering grammar or relative clauses.